Globalisation of natural gas markets - effects on prices and trade patterns - Finn Roar Aune; Knut Einar Rosendahl; Eirik Lund Sagen (Statistics Norway, Research Department, 2008)
The regional natural gas markets are expected to gradually become more integrated. The major driving forces are lower LNG costs, more spot trade, and increased need for imports into the US and other key markets. In this paper we examine various scenarios for a future global gas market, particularly focusing on natural gas prices and trade patterns. We use a numerical model of the international energy markets, with detailed modelling of regional gas production and international gas transport. Scenarios with different assumptions about future demand and supply conditions are simulated. Our results suggest that trade between continents will grow considerably over the next couple of decades, and that prices in the main import regions will remain around current levels. However, significant constraints on exports from the Middle East may alter this picture.
Keywords: C61; F17; L95; Q31; 330; Natural gas trade; gas prices; numerical model